Zooman Sam - Lowry, Lois.; De Groat, Diane (Boston : Houghton Mifflin, 1999)
Four-year-old Sam's appearance as a zookeeper at his nursery school's Future Job Day leads him to a number of exciting activities and discoveries, including reading.
"Walter Lorraine Books.".
School Library Journal, September 1999.
Booklist, July 1999.
New York Times, February 2000.
Horn Book, September 1999.
Bulletin (Center for Children's books), September 1999.
Keywords: Occupations -- Fiction; Zoo keepers -- Fiction; Nursery schools -- Fiction; Schools -- Fiction; Literacy -- Fiction; Occupations -- Fiction; Zoo keepers -- Fiction; Nursery schools -- Fiction; School stories; Literacy -- Fiction; Occupations -- Fiction; Zoo keepers -- Fiction; Nursery schools -- Fiction; Schools -- Fiction; Literacy -- Fiction